From full-scale testing of steel lattice towers to stochastic reliability analysis - Szafran, J.; Kamiński, M. (Archives of Mechanics, 2017)
analysis of the steel lattice telecommunication structure exposed to the wind pressure, whose average value is treated as the Gaussian random variable. The Least Squares Method is provided here for symbolic recovery of the polynomial responses of this structure in addition to the given uncertainty source and it serves to the twentieth order perturbation-based approximations for the first four probabilistic moments and coefficients. Static numerical analysis has been carried out by the use of the incremental BFGS (Broyden–Fletcher–Goldfarb–Shanno) procedure necessary for the so-called P-delta effect in steel structures, while the basic statistics of the ultimate limit state have been included into the formulas for the reliability indices of both first and second order. This study shows that the safety margin of such structures is definitely wider than it follows the basic Eurocodes statements, which means that designed durability period for these telecommunication structures is definitely longer.